Automatic Modal Wavefront Estimation and Correction for Optical Aberration - Xiaomin Lai; Chen Xu; Yafeng Liu; Kaihua Wei; Kaihua Wu (IEEE Photonics Journal)
Modal estimation of aberration can quantify the amount of aberration, which plays an important role in optical system optimization, aberration correction, and so on. Here, we propose a simple but effective method to find the modal wavefront of aberration. Once the aberrated wavefront has been detected, it will be automatically analyzed with a method based on one-dimensional standard polynomial fitting. According to the analysis, the modal wavefront and the property of aberration can be obtained for further studies. Here, for example, we show that it can be used to calculate the optimal correction wavefront. Experiments were implemented to testify the correctness and effectiveness of this method. This method provides users another option for aberration interpretation.